Highly Sensitive Detection Method for HV69-70del in SARS-CoV-2 Alpha and Omicron Variants Based on CRISPR/Cas13a - Niu, Mengwei; Han, Yao; Dong, Xue; Yang, Lan; Li, Fan; Zhang, Youcui; Hu, Qiang; Xia, Xueshan; Li, Hao; Sun, Yansong (Frontiers in Bioengineering and Biotechnology, 2022)
As SARS-CoV-2 variants continue to evolve, identifying variants with adaptive diagnostic tool is critical to containing the ongoing COVID-19 pandemic. Herein, we establish a highly sensitive and portable on-site detection method for the HV69-70del which exist in SARS-CoV-2 Alpha and Omicron variants using a PCR-based CRISPR/Cas13a detection system (PCR-CRISPR). The specific crRNA (CRISPR RNA) targeting the HV69-70del is screened using the fluorescence-based CRISPR assay, and the sensitivity and specificity of this method are evaluated using diluted nucleic acids of SARS-CoV-2 variants and other pathogens. The results show that the PCR-CRISPR detection method can detect 1 copies/μL SARS-CoV-2 HV69-70del mutant RNA and identify 0.1% of mutant RNA in mixed samples, which is more sensitive than the RT-qPCR based commercial SARS-CoV-2 variants detection kits and sanger sequencing. And it has no cross reactivity with ten other pathogens nucleic acids. Additionally, by combined with our previously developed ERASE (Easy-Readout and Sensitive Enhanced) lateral flow strip suitable for CRISPR detection, we provide a novel diagnosis tool to identify SARS-CoV-2 variants in primary and resource-limited medical institutions without professional and expensive fluorescent detector.